(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2014)
This article gives a brief account of the establishment and development of the right to make amendments in the legislative process during the Spanish period called “Restoration” as also the limitations imposed on its exercise, based on the 1838, 1847 and 1918 Spanish Congress Standing Orders, in order to contribute to a better understanding of the current enmendandi ius.